The effects of laser procedure in symptomatic patients with haemorrhoids: A systematic review - Torrinha, Gonçalo; Gonçalves, Tatiana; Sousa, Maria; Högemann, Gerrit; Goulart, André; Carvalho, Alexandre Fernandes; Leão, Pedro (Frontiers in Surgery, 2022)
Purpose Haemorrhoids are normal structures in the human body, only seen as pathological when symptomatic. Nowadays, new techniques have surfaced using a diode laser which, after locating the target arteries, blocks the blood flow while hitting and shrinking the local mucosa/submucosa at a depth of 4 mm. Our work aimed to give a broad view over this new technique and its consequences in the post-operative follow-up with a systematic review. Methods EMBASE and MEDLINE databases were consulted, retrieving clinical trials, which mentioned the use of 980 nm diode laser on the treatment of haemorrhoids. Results Ten clinical trials analyzing the post-operative effects of laser haemorrhoidectomy were selected, including 2 randomized controlled clinical trials and 1 controlled clinical trial. The overall quality of the trials was low, indicating a high risk of bias. Conclusion The laser haemorrhoidectomy procedure revealed a high therapeutic potential, considering the reduced number of postoperative complaints (bleeding/pain), the high symptom resolution and the reduced recurrence, albeit the high heterogeneity between the studies in terms of reported results. Future investigations with higher quality and controlled double-blinded studies obtaining better-categorized results should be conducted in order to better evaluate this procedure and compare it to the current paradigm.